1991
DOI: 10.1016/0014-5793(91)80989-g
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the PKC‐isotypes α, β1, γ, δ, and ε by phorbol esters of different biological activities

Abstract: Phorbol esters, tctradecanoylphorbolacetate, sapintoxin-A, 1%deoxyphorbol-phenylacctate, I2-dcoxyphorbol-phenylacetate-20_acctate, thyrneleatoxin and resinifcratoxin were investigated for their abilities to activate the PKC-isotypes a, b,, y, 6 and E. PKC-isotypes were grouped into two classes on the basis of Ca" requirements for activation by phorbol esters; 01, /3,, and y being Ca a+-dependent forms and S and E being Ca2+-indepcndent. PKC-isotype selective activation by phorbol esters was observed in that SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(115 citation statements)
references
References 26 publications
4
111
0
Order By: Relevance
“…In separate experiments, phenylephrine-precontracted PA rings (n ϭ 5) were incubated in the presence of the PKC activator thymeleatoxin (THX, 1 mol/l) for 60 min. THX has been demonstrated to be an effective activator of multiple PKC isozymes (25,26).…”
Section: Animalsmentioning
confidence: 99%
“…In separate experiments, phenylephrine-precontracted PA rings (n ϭ 5) were incubated in the presence of the PKC activator thymeleatoxin (THX, 1 mol/l) for 60 min. THX has been demonstrated to be an effective activator of multiple PKC isozymes (25,26).…”
Section: Animalsmentioning
confidence: 99%
“…Various phorbol ester and related promoters, proin¯ammatory agents and irritants are able to mimic the e ect of diacylglycerol in vitro and cause activation of PKC (at least the cPKC and nPKC subfamilies; see for example Ryves et al, 1991). However in vivo, the slow metabolism of these pharmacological PKC activators distinguishes the temporal pattern of responses both by maintaining activation of PKC over prolonged periods and by causing increased proteolysis of PKC and hence its downregulation (Young et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Rsk activation can be promoted by multiple signaling pathways in cancer cells, including those triggered by steroids, insulin, EGF, and estrogen (10,(12)(13)(14)(15). Additionally, Rsk activation can be triggered by PKC signaling [via the PKC/rapidly accelerated fibrosarcoma (RAF)/mitogen-activated protein kinases (MAPK) pathway], which is activated by phorbol12-myristate13-acetate (PMA) (16,17). Previous studies have found that Rsk2 is overexpressed in 50% of breast cancers and prostate tumors (18,19), and Rsk signaling has been implicated in the regulation of survival, anchorage-independent growth, and transformation of breast cancer cells in culture (20).…”
mentioning
confidence: 99%